Matematyka
galactikos
2017-09-28 20:12:37
Witam Proszę o pomoc w rozwiązaniu zadania 4 z załącznika. Odwdzięczę się
Odpowiedź
kielbasa112
2017-09-28 23:41:55

a) (-2x³-3)-(-2x³-3x²-2x-3)  // x= 1  (-2x³-3)-(-2x³-3x²-2x-3) = -2x³-3+2x³+3x²+2x+3= 3x²+2x 3x²+2x= 3*1³+ 2*1= 3*1+2*1= 3+2= 5 b) -(7/8x²+5x-9 1/3)+(-3x- 3 1/8x²)- 9 1/3  // x=-2  -(7/8x²+5x-9 1/3)+(-3x- 3 1/8x²)- 9 1/3 = -7/8x²- 5x+9 1/3- 3x- 3 1/8x²-9 1/3=  = -1 1/8x²- 8x - 3 1/8x²= -8x-4 2/8x²= -4 1/4x²-8x -4 1/4x²-8x= -4 1/4 *(-2)²- 8 *(-2)= - 17/4* 4+16= -17+16= -1

Dodaj swoją odpowiedź